Unveiling different structural orderings in Fe5-xGeTe2 - Walve, Vaibhav; Parakh, Piyush; Rajput, Umashankar; Mhase, Akash S.; Singh, Kirandeep; Deshpande, Aparna (Physical Review B, 2024)
We investigate the metallic van der Waals itinerant ferromagnet Fe5-xGeTe2 5 - x GeTe 2 with atomic scale, spatially resolved low-temperature scanning tunneling microscopy (STM), and spectroscopy (STS). STM images unveil / / a new structural order 2a a x 1a a along with the known order 3a a x 3a a manifesting as nonuniform domains. STS shows spatial and energy resolved local density of states that reveal the crucial influence of Fe(1) site occupancy on the system's electronic interactions. Our magnetization measurements show magnetic anomalies at lower temperatures and identify a Curie temperature (Tc) c ) surpassing room temperature. Collectively, our results elucidate the intricate nature of Fe5-xGeTe2 5 - x GeTe 2 and underscore its potential for tunability of spintronics and high-temperature magnetic applications.